2018
DOI: 10.1177/0046958018794993
|View full text |Cite
|
Sign up to set email alerts
|

Financial Impact of Incentive Spirometry

Abstract: Despite largely unproven clinical effectiveness, incentive spirometry (IS) is widely used in an effort to reduce postoperative pulmonary complications. The objective of the study is to evaluate the financial impact of implementing IS. The amount of time nurses and RTs spend each day doing IS-related activities was assessed utilizing an online survey distributed to the relevant national nursing and respiratory therapists (RT) societies along with questionnaire that was prospectively collected every day for 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…25 Although this may be true, the clinical reality is that providing more patient training and encouraging more frequent use will come at a cost, in addition to the cost of the devices, which may become difficult to justify in the context of numerous studies questioning the clinical benefit of IS. Eltorai et al 26 evaluated the financial impact of implementing IS using prospective questionnaires to evaluate the time spent by health professionals doing ISrelated activities and national survey work load data. The authors estimated that the total annual cost of implementing postoperative IS to be $1.04 billion (95% CI $949.4 million to $1.13 billion).…”
Section: Should We Persevere With Is In Postoperativementioning
confidence: 99%
“…25 Although this may be true, the clinical reality is that providing more patient training and encouraging more frequent use will come at a cost, in addition to the cost of the devices, which may become difficult to justify in the context of numerous studies questioning the clinical benefit of IS. Eltorai et al 26 evaluated the financial impact of implementing IS using prospective questionnaires to evaluate the time spent by health professionals doing ISrelated activities and national survey work load data. The authors estimated that the total annual cost of implementing postoperative IS to be $1.04 billion (95% CI $949.4 million to $1.13 billion).…”
Section: Should We Persevere With Is In Postoperativementioning
confidence: 99%
“…Atelectasis also affects 90% of patients who have undergone general anesthesia, thus incentive spirometers are commonly used in patients recovering from surgery under general anesthesia or bedridden for prolonged periods of time [3][4]. Adding to the widespread need for the device, it was found that incentive spirometers are used in over 95% of US hospitals after surgery [5]. These statistics illustrate the ubiquity of respiratory conditions and the increased need for incentive spirometers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are approximately 9.7 million inpatient surgeries each year in the US. These numbers indicate that the total annual cost of incentive spirometers surpasses $1 billion [5]. This value signifies the issues of overtreatment and wasted spending in the US medical industry and thus, there is an opportunity for a cheaper alternative to incentive spirometers that would lower the annual implementation costs for hospitals across the globe.…”
Section: Introductionmentioning
confidence: 99%
“…Incentive spirometry (IS) is commonly prescribed to reduce respiratory complications [1][2][3]. IS ( Figure 1) works by expanding alveoli through maximal inspiration to prevent atelectasis.…”
Section: Introductionmentioning
confidence: 99%